Community-based mortality surveillance among internally displaced vulnerable populations in Banadir region, Somalia, 2022–2023 - Adam, Mohamed Hussein; Garba, Bashiru; Dahie, Hassan Abdullahi; Baruch, Joaquin; Polonsky, Jonathan A.; Hassan, Jihaan; Mohamoud, Jamal Hassan; Ali, Dahir Abdi; Malik, S. K. Md Mamunur Rahman; Checchi, Francesco; Dirie, Najib Isse (Frontiers in Public Health, 2025)
Somalia faces a severe humanitarian crisis driven by conflict, drought, and rising food prices, straining its fragile health system. Internally displaced persons (IDPs) suffer high mortality rates, yet data on causes of death remain limited. This study integrates verbal autopsy (VA) with community-based surveillance (CBS) to identify mortality causes in IDP populations. A hybrid retrospective-prospective mortality surveillance study was conducted in 57 IDP camps across Daynile and Kahda districts, Banadir region, from October 2022 to November 2023. Retrospective baseline data from 20,323 individuals were collected in January–February 2023, followed by prospective surveillance rounds in March, April, and May–November 2023. Causes of death were determined using WHO-standardized VA methods. During the retrospective period, Daynile had a CDR of 3.15 per 10,000 person-time, while Kahda’s was 1.26. Mortality rates fluctuated, showing significant reductions at certain times. Over the prospective data collection period, the overall CDR was 0.64 per 10,000 person-time. Verbal autopsies revealed that severe malnutrition, respiratory infections, and diarrheal diseases were the leading causes of death. Among children under five, malnutrition, measles, and neonatal pneumonia were the primary causes. Our study highlights the severe impact of malnutrition and infectious diseases on mortality rates among IDPs in Banadir. Continuous surveillance and targeted health interventions are crucial to address the ongoing humanitarian crisis in Somalia. Enhancing training for data collectors and fostering community engagement can improve data accuracy and support timely humanitarian responses.